SYNTHESIS AND ACETYLCHOLINESTERASE/BUTYRYLCHOLINESTERASE INHIBITION ACTIVITY OF ARECOLINE-, 4-THIAZOLIDINONE- AND PIPERIDINE- BASED CONJUGATES - Sharath Kumar, Kothanahally Shivaramu; Mohan, Chakrabhavi Dhananjaya; Jagadish, Swamy; Rakesh, KODAGAHALLI SATHYA; Hanumappa, Ananda; Basappa; Rangappa, KANCHUGARAKOPPAL SUBBEGOWDA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The aim of the study is to design, synthesize and identification of novel acetylcholinesterase/butyrylcholinesterase (AChE/BuChE) inhibitors. Methods: The AChE and BuChE inhibition activity of a library of piperidine and 4-thiazolidinone substituted arecoline derivatives are described. The chemical structures of newly synthesized compounds were confirmed by IR, 1H NMR, 13C NMR and mass spectral analysis. Results: The cholinesterase inhibition assays indicated that few of the synthesized compounds exhibited considerable activity at micromolar range for AChE over BuChE. Compound 7c exhibited the most potent AChE inhibitory activity with an IC50 value of 6.62 Î¼M for AChE and 13.78 Î¼M for BuChE, which is comparable to the standard Neostigmine with an IC50 2.05 Î¼M for AChE and 3.64 Î¼M for BuChE respectively. Conclusion: Our results clearly demonstrate that arecoline-4-thiazolidinone derivatives open up a new avenue in the field of Alzheimer’s disease. Keywords: Arecoline analogs, Propylphosphonic anhydride (T3PÂ®), Acetylcholinesterase/butyrylcholinesterase inhibitor, 4-thiazolidinones.